Assessment of exceptional students : educational and psychological procedures - Taylor, Ronald (b)
Assessment of Exceptional Students, Seventh Edition, offers a practical approach that emphasizes how both informal and formal procedures fit into the overall assessment process.
Includes references and index.
Keywords: Children with disabilities Education; Children with disabilities Psychological testing